SISTEM PEMILIHAN UMUM ANGGOTA DEWAN PERWAKILAN RAKYAT DALAM PERSPEKTIF PASAL 1 AYAT 2 UNDANG-UNDANG DASAR 1945 - Wahyu Utama; Dessy Artina; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The Proportional Election System is a system in which one electoraldistrict elects several representatives. The proportional system is also called abalanced system, there are two types of systems in the proportional system,namely the open proportional system and the closed proportional system. OpenProportional System is an electoral system in which voters directly elect theirlegislative representatives. Whereas in a closed proportional system, voters onlychoose their political party. The formulation of the problem in this study is whatare the advantages and disadvantages of open and closed proportional systemsand whether the system is most appropriate to be applied to legislative electionsin Indonesia.This study uses normative legal research methods. This study also usesthree sources of legal materials, namely, primary, secondary and tertiary legalmaterials. The purpose of this study is to determine the advantages anddisadvantages of open and closed proportional systems and to find out the mostappropriate system to be applied to legislative elections in Indonesia. Legislationwhich is the main source of this research is the 1945 Constitution, Law number 7of 2017 concerning General Elections.The results obtained from this study are that open and closed proportionalsystems have advantages and disadvantages, so the appropriate election system tobe used in Indonesia is the Open Election System because voters can choosecandidates who have the same ideas, vision and mission, reflecting the profile ofall the people, increasing public enthusiasm to participate in elections,prioritizing the unity and integrity of the Indonesian nation.Keywords: Proportional System, general elections, People.